STRATEGY TO IMPROVE THE COMPETENCE OF PRIVATE UNIVERSITY LECTURERS IN KENDARI: A DESCRIPTIVE QUALITATIVE APPROACH - Jumanudin, Jumanudin; Mokodompit, Eliyanti Agus (Penelitian dan Pengembangan Ilmu, 2024)
Increasing the competence of lecturers in higher education is a crucial factor in improving the quality of higher education in Indonesia. Private universities in Kendari, although they have implemented various policies to develop lecturer competencies, still face challenges in implementing policies that are effective and in accordance with the specific needs of each study program. One of the research gaps found is the limited resources, both budget and time, which hinder the development of lecturer competencies in a sustainable and structured manner. This study uses a qualitative descriptive approach with in-depth interviews with five key informants to explore the policies and strategies applied in the development of lecturer competencies in private universities in Kendari. The findings of this study contribute to enriching the literature on lecturer competency development policies, as well as providing practical insights for university management in designing training programs that are more flexible and integrated with the specific needs of disciplines. The implications of this study are the importance of adjusting lecturer competency development policies that are more adaptive to the challenges faced, as well as the need for continuous evaluation to increase the effectiveness of the program.